Rancangan Sistem Pakar Perawatan Strawberi Pada Desa Ronga-Ronga Kabupaten Bener Meriah - Zulfa, Ira; Wahyuni, Maulia (Universitas Gajah Putih, Indonesia, 2023)
One of the strawberry plant species, Fragaria chiloensis L, has spread to various countries in America, Europe and Asia. In the maintenance of strawberry plants, one of the obstacles that are often faced is disease. Disease is a condition where the plant is disturbed or hampered which is caused not from pests, it will cause several shortcomings including our lack of knowledge in plant care, the number of crop failures in plants and the decline in sales prices due to failed harvest quality. Therefore, several solutions are needed, such as: (1) Creating a system to provide information to farmers in caring for strawberry plants. (2) Make it easier for the community and farmers to find web-based information to increase their crop yields, and (3) improve the quality of their crop yields so that the sales value increases.